Optimization and design of pigments for heat-insulating coatings - 王广海 张跃 (Chinese physics B, 2010)
This paper reports that heat insulating property of infrared reflective coatings is obtained through the use of pigments which diffuse near-infrared thermal radiation. Suitable structure and size distribution of pigments would attain maximum diffuse infrared radiation and reduce the pigment volume concentration required. The optimum structure and size range of pigments for reflective infrared coatings are studied by using Kubelka-Munk theory, Mie model and independent scattering approximation. Taking titania particle as the pigment embedded in an inorganic coating, the computational results show that core-shell particles present excellent scattering ability, more so than solid and hollow spherical particles. The optimum radius range of core-shell particles is around 0.3 - 1.6 μm. ~rthermore, the influence of shell thickness on optical parameters of the coating is also obvious and the optimal thickness of shell is 100-300 nm.